Detection of Mycobacterium avium subspecies Paratuberculosis (MAP) from goats of Jabalpur Region in India - Jatav, Maneesh; Verma, Yamini; Swamy, Madhu; Dubey, Amita (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Paratuberculosis or John’s disease (JD) is one of the major economically important diseases of small ruminants worldwide. The disease is  caused by Mycobacterium avium subspecies paratuberculosis (MAP). The present study was carried out to detect Mycobacterium avium subspecies paratuberculosis from goats of the Jabalpur region. The study was conducted for eight months, from July 2017 to February 2018.  Goats of either sex, above 6 months of age, belonging to different breeds were selected for this study. Total 230 samples (160 faecal and  70 tissues) were stained by Z-N staining method. The study revealed that 5% fecal and 7.14 % tissue samples were found positive for MAP.
Keywords: Acid-fast bacilli Goats; Jabalpur; Paratuberculosis; ZiehlNeelsen